Biliary complications of cystic fibrosis. Issue 3 (March 1992) - O'Brien, S; Keogan, M; Casey, M; Duffy, G; McErlean, D; Fitzgerald, M X; Hegarty, J E
Abstract : One hundred and four adult patients with cystic fibrosis were evaluated for the presence of liver disease as defined by abnormal liver function tests of six months' duration, histological evidence of fibrosis or cirrhosis, or the presence of portal hypertension, or both. Twenty patients fulfilled these criteria and were evaluated further for the presence of biliary tract abnormalities with biliary scintigraphy using 99Tc diisopropylphenyl-carboxymethyl iminodiacetic acid (DISIDA) and endoscopic retrograde cholangiography. Clearance of 99Tc DISIDA from the liver and biliary tree was diminished at 45 (E45) and 60 (E60) minutes in the patients with liver disease compared with those without liver disease; E45 = 37.8% and 65.8%, p less than 0.01; E60 = 48.2% and 77.5%, p less than 0.01 respectively. Serial analogue images of the extrahepatic biliary tree were consistent with common bile duct obstruction with retention of DISIDA and tapering of the common bile duct in seven of 18 patients with and two of 10 patients without liver disease. Endoscopic retrograde cholangiography showed changes consistent with sclerosing cholangitis, with beading and stricturing of the intrahepatic ducts in 12 of the 14 patients. In all 14 patients, including those in whom biliary scintigraphy had suggested obstruction, no abnormality of the common bile duct was identified. These results indicate that abnormalities of the bile ducts in patients with cystic fibrosis related liver disease are confined to the intrahepatic biliary tree and that common bile duct strictures do not contribute to either the progression or development of liver disease in these patients.